2021
DOI: 10.1021/acsanm.1c02724
|View full text |Cite
|
Sign up to set email alerts
|

BaTiO3@C Core–Shell Nanoparticle/Paraffin Composites for Wide-Band Microwave Absorption

Abstract: BaTiO 3 @C nanoparticles with a core−shell nanostructure were synthesized through a facile hydrothermal and dopamine carbonization process. The microstructure of nanoparticles and microwave absorption performance of the nanoparticle/ paraffin composite were systematically investigated. Dense heterogeneous interfaces and conductive carbon shells are formed on the surfaces of the BaTiO 3 nanoparticles. The enhanced interfacial polarization, dipole polarization, and conductive loss contribute to the improved micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The morphology was further analyzed by referring to extensive literature. 32,33 The integrated core, as observed in FFm-400 and FFm-500, is found transformed into locally connected fine spheres, when a high reduction temperature of 600 °C is applied. This morphology variation of the core indicates that Fe particles generated from hydrogen-thermal annealing begin to agglomerate, as shown in Figure 2e.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The morphology was further analyzed by referring to extensive literature. 32,33 The integrated core, as observed in FFm-400 and FFm-500, is found transformed into locally connected fine spheres, when a high reduction temperature of 600 °C is applied. This morphology variation of the core indicates that Fe particles generated from hydrogen-thermal annealing begin to agglomerate, as shown in Figure 2e.…”
Section: Resultsmentioning
confidence: 89%
“…The HRTEM image in Figure f shows that the interplanar distance of the crystal measured at two sites is 1.68 and 2.46 Å, matching well to the (220) lattice plane of Fe 3 O 4 and (110) lattice plane of Fe, respectively. The morphology was further analyzed by referring to extensive literature. , The integrated core, as observed in FFm-400 and FFm-500, is found transformed into locally connected fine spheres, when a high reduction temperature of 600 °C is applied. This morphology variation of the core indicates that Fe particles generated from hydrogen-thermal annealing begin to agglomerate, as shown in Figure e.…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of wide intensity fluctuation at low degree was attributed to the amorphous carbon shell in BT@C 4 and BT@N-C 4 . 38 FTIR spectra are shown in Fig. 3b.…”
Section: Resultsmentioning
confidence: 99%
“…Two bands centered at 1353 cm −1 (D band) and 1581 cm −1 (G band) were observed for all samples, which confirmed that g-C 3 N 4 was successfully converted into amorphous carbon with the catalytic reaction of Ni nanoparticles at high temperature. In general, the D band was attributed to the sp 3 -hybridized carbon atoms, representing the degree of defects and disorder within the material. In addition, the appearance of the G band provided strong proof for the existence of graphitic carbon.…”
Section: Preparation Of Cocklebur-likementioning
confidence: 99%
“…The rapid development of 5G communication technology and various miniaturized electronic devices have greatly enriched our daily life. However, the resulting electromagnetic radiation brings great harm to our health. Generally, an ideal microwave absorber should have the advantages of thin thickness, wide bandwidth, low density, and strong absorption. However, it is difficult for a single-loss type or single-component absorber to achieve ideal absorption, so it is particularly important to construct heterostructures to realize the synergistic effect of multiple loss modes and components. …”
Section: Introductionmentioning
confidence: 99%